2019
DOI: 10.20944/preprints201901.0064.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cancer Aneuploidy Paradox: In the Light of Evolution

Abstract: Aneuploidy should compromise cellular proliferation but paradoxically favours tumour progression and poor prognosis. Here, we consider this paradox in terms of our most recent observations of chemo/radio-resistant cells undergoing reversible polyploidy. The latter perform segregation of two parental groups of end-to-end linked dyads by pseudo-mitosis creating tetraploid cells through a dysfunctional spindle. This is followed by autokaryogamy and homologous pairing preceding a bi-looped endo-prophase. The assoc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 89 publications
(134 reference statements)
0
8
0
Order By: Relevance
“…,b; Salmina et al. ). One of the depolyploidization mechanism implemented by tumour cells is the elimination of “excessive” chromatin by its extrusion from the nucleus into the cytoplasm.…”
Section: Discussionmentioning
confidence: 96%
“…,b; Salmina et al. ). One of the depolyploidization mechanism implemented by tumour cells is the elimination of “excessive” chromatin by its extrusion from the nucleus into the cytoplasm.…”
Section: Discussionmentioning
confidence: 96%
“…DMC1 mediates interhomolog DNA strand invasion [124] and is required for meiotic crossovers [125]. Recent studies have demonstrated that the DMC1 protein is ectopically expressed in Sézary patient lymphocytes [8], CTCL biopsy samples [24], cervical, colon and breast cancer cell lines [126][127][128], as well as in glioblastoma [129]. In addition, DMC1 mRNA expression has been observed in Burkitt's lymphoma and human lymphoblastoid cell lines [130].…”
Section: Dmc1mentioning
confidence: 99%
“…In addition, DMC1 mRNA expression has been observed in Burkitt's lymphoma and human lymphoblastoid cell lines [130]. Interestingly, the upregulation of the DMC1 protein and mRNA was shown in several cell lines in response to irradiation-induced DSB formation and damage repair [126][127][128][129][130]. Ionizing radiation (IR) produces reactive oxygen species in proliferating cancer cells that leads to the generation of DSBs and activation of HR or NHEJ repair pathways [129,131,132].…”
Section: Dmc1mentioning
confidence: 99%
See 1 more Smart Citation
“…It is nowadays viewed as a kind of parasexual somatic reduction division, which transforms senescence cells into neoplastic ones and therefore plays and important role, especially in the formation, maintenance and progression of particular types of epithelial tumors. Analogous to meiotic recombination events, the reactivation of a meiotic program in mitotic somatic cells, meiomitosis, generates DNA double strand breaks that instigate repair activities, which in turn fabricate a plethora of structural rearrangements (Kalejs et al, 2006;Grichnik, 2008;Ianzini et al, 2009;Lindsey et al, 2013;Walen, 2014;Tsang et al, 2018;Salmina et al, 2019b).…”
Section: and Beyond: Re-fusion Entosis Neosis Meiomitosis And Polyploidizationmentioning
confidence: 99%